EDA ligand triggers plasma membrane trafficking of its receptor EDAR via PKA activation and SNAP23-containing complexes - Yao, Yuyuan; Yang, Ruihan; Zhu, Jian; Schlessinger, David; Sima, Jian (Cell & bioscience, 2023)
Background Ectodysplasin-A (EDA), a skin-specific TNF ligand, interacts with its membrane receptor EDAR to trigger EDA signaling in skin appendage formation. Gene mutations in EDA signaling cause Anhidrotic/Hypohidrotic Ectodermal Dysplasia (A/HED), which affects the formation of skin appendages including hair, teeth, and several exocrine glands. Results We report that EDA triggers the translocation of its receptor EDAR from a cytosolic compartment into the plasma membrane. We use protein affinity purification to show that upon EDA stimulation EDAR associates with SNAP23-STX6-VAMP1/2/3 vesicle trafficking complexes. We find that EDA-dependent PKA activation is critical for the association. Notably, either of two HED-linked EDAR mutations, T346M and R420W, prevents EDA-induced EDAR translocation; and both EDA-induced PKA activation and SNAP23 are required for Meibomian gland (MG) growth in a skin appendage model. Conclusions Overall, in a novel regulatory mechanism, EDA increases plasma membrane translocation of its own receptor EDAR, augmenting EDA-EDAR signaling in skin appendage formation. Our findings also provide PKA and SNAP23 as potential targets for the intervention of HED.